Prophylactic and biocontrol effect of the microencapsulated lactic acid bacteria extracted from honey bee gut against some diseases of the honey bee, Apis mellifera L. - Fatma Mahmoud; Rasha M. A. Farag; Shireen A. M. Ma’moun; Ahmed S. Abou Zeid; Akila M. El Shafei; Eman E. Essa (Egyptian Journal of Biological Pest Control)
Abstract Background American foulbrood (AFB), Nosemosis and Varroasis are diseases that affect honey bee health and their products. The present study evaluated microencapsulated lactic acid bacteria (LAB) as a novel technique for the biocontrol of these diseases. Double coated microencapsulation was performed for the preservation of five different locally isolated, honey bee endogenous LABs (Lactobacillus plantarum MK780211, L. plantarum MK780215, L. kunkeei MK780216, L. kunkeei MK780218, and Lactobacillus sp. MK780212). Results In vivo, twenty-seven colonies of honey bees of equal strength and queens of the same age were divided into seven treatments and compared with a control. There were different observations on the honey bee colonies according to their treatments. Honey bee colonies that were supplied with LAB microcapsules alternatively; with Fumidil®B and with formic acid had the highest increase in growth curves. The treatments that had a moderate increase in growth curves were the honey bee colonies treated with LAB microcapsules only and LAB microcapsules alternatively with Sulphamethoxazole, with Thymol, with both “Sulphamethoxazole and Thymol” and with both “Fumidil®B and Thymol”. Finally, honey bee colonies that were supplied with Sulphamethoxazole, Thymol, Fumidil®B and formic acid without LAB microcapsules (−ve control) had a slight increase in growth curves that was lower than normal. The honey bee colonies without any treatments (+ ve control) collapsed since the first three months of the experiment. Conclusion Honey bee colonies could be supplemented with microencapsulated LABs, alternatively with low concentrations of traditional honeybee treatments such as Fumidil®B and formic acid to achieve maximum protection from diseases.